Development of The E-Personal Safety Logbook (e-PSLB) Optimization Registration Process of Personnel Onboard FSRU - Faishal Rachman; Andri Cahyadi; Rachmat Afriyanto (Institut Teknologi Sepuluh Nopember, 2020)
PT PGN LNG Indonesia (PGN LNG) aims to develop the LNG business that consists of natural gas liquefaction, LNG storage and shipment, and regasification to natural gas. Since July 2014, PGN LNG has been operating Floating Storage Regasification Unit (FSRU) which located 21km offshore from Lampung. In order to support PGN LNG operation on FSRU related to requirement of Health, Safety, Security and Environment (HSSE) data of personnel onboard vessel, PGN LNG developed a system to mitigate potential hazards and risk that called Personal Safety Logbook (PSLB). PSLB consist of personnel data of identity, basic sea survival certificate, and health. Since July 2014 to December 2016 registration of PSLB data done manually by collecting registration paper filled by applicant and approved by management. Based on the evaluation conducted by management, it showed implementation of manual registration requires long approval time. In this case, PGN LNG require system that reduces approval time and provides comprehensive information. In July 2016, Department HSSE has been developed an online e-PSLB Application that started to be implemented in January 2017. Until December 2019 it has already done 846 PSLB submissions with an average 282 per year. Based on the analysis of the data, it showed that if still using manual PSLB Registration in the period of January 2017 until December 2019 it is required total cost of Rp.333,630,000 in three years. Whereas when compared with the use of e-PSLB within same period, it is required a total cost of Rp176,846,741. In addition, reviewed from the completion duration of one Manual PSLB takes 3 hours 15 minutes, while e-PSLB only takes 45 minutes. Therefore, based on the results of the analysis of e-PSLB proved effective and efficient in assisting operation excellence of PGN LNG.